The demarcation of the first pericope of Joel in Hebrew and Greek manuscripts : a comparison of ancient and modern scholars - Scharneck, R. (Journal for semitics, 2010)
The first pericope division of the book of Joel is problematic. There is a great deal of disagreement among scholars and Bible translators about where the text should be demarcated. Consequently, this article attempts to answer questions such as: What is the most acceptable division for the book of Joel? What are the implications of the different divisions on the understanding of the text? This article refers to the divisions of Joel made in various ancient manuscripts. This is done in an attempt to establish how the ancients interpreted the text. When that understanding is established, it is compared to the understanding of modern scholars. It is believed that this might lead to new insights regarding the interpretation of, especially, the first chapter of the book of Joel.